Heating and Cooling with Heat Pumps – Projects developed in Mexico - Rivas-Cruz, Fernando; Hernández-Martínez, Eduardo Gamaliel; Papadimitriou-Suarez del Real, Luis Enrique (Renewable Energy, Biomass & Sustainability, 2021)
This article presents extensive research work on geothermal and aerothermal heat pump systems developed in Mexico. Seven systems are presented: (a) water-water geothermal heat pump for a kindergarten and a water-air and water-water combo geothermal heat pumps for a Hospital for the Mexican Social Security Institute (IMSS) at Los Humeros community in Puebla, both systems working for heating; (b) three water-air geothermal heat pumps for heating/cooling for a laboratory complex at Mexicali B.C.; (c) one water-air geothermal heat pump for cooling for a meeting room at Cuernavaca Morelos; (d) two water-water geothermal heat pumps for pool heating at a Sports Club, and four air-water aerothermal heat pumps for cooling/heating and water heating at a hotel in Aguascalientes, Aguascalientes; and (e) a hybrid system composed of two air-water aerothermal heat pumps and a photovoltaic system in León, Guanajuato.